First-Principles Study Of The Structural, Stability And Electronic Properties Of Small Aluminum-Titanium-Nickel Clusters - Koh, Pin Wai (2021)
Nanocluster has been a system of interest for the past decades due to its peculiar size-dependent properties as compared to its bulk counterparts, e.g. the chemical and electronic properties between the buckminsterfullerene C60 and graphene. However, computational, theoretical and experimental studies for pure and binary element small-size clusters are scarce, not to mention of small-size ternary element clusters. For the case of aluminium-titanium-nickel (Al-Ti-Ni) ternary element clusters, published works of small Al-Ti-Ni clusters mostly come from Erkoc and Oymak (2003; 2002, 2004) by using a fundamental empirical potential in molecular dynamic techniques, followed by performing a single point optimization at DFT level to obtain the ground-state structure for the cluster. The Al-Ti-Ni clusters generically have a very different mechanical and catalytic properties compared to their bulk counterparts, as stated in the articles by Erkoc and Oymak (2003; 2002, 2004). However, information and data about the catalytic and mechanical properties Al-Ti-Ni clusters are not shown in their articles. One of the reasons for this to have happened is that most of the ground-state structure of the binary of ternary element Al-Ti-Ni clusters that shown in their article are lack of experimental data supports. This thesis reports a systematic study of the computational modelling of small-size Al-Ti-Ni clusters at the atomistic level using a tactical two-stage computational strategy and a multitude of theoretical tools. The main focus of this thesis is to perform a systematic and thorough study on selected properties of the AlxTiyNiz clusters at the lowest energy state, where x, y and z are non-negative integers such that x + y + z = 4, 5 and 6. The ground state energy configurations of the clusters are obtained by performing a purpose-designed two-stage optimization.